폐활성 슬러지로부터 생물학적 수소 생산을 위한 최적 조건 연구 - 김동건(Dong Kun Kim); 이윤지(Yun Jie Lee); 유명진(Myong Jin Yu); 박대원(Dae Won Pak); 김미선(Mi Sun Kim); 상병인(Byoung In Sang) (Daehan hwan'gyeong gonghag hoeji, 2006)
Waste activated sludge(WAS) collected from domestic wastewater treatment plant is biomass that contains large quantities of organic matter. However, relevant literature show that the bio-hydrogen yield using WAS was too low. In this study, the effect of pretreatment of WAS on hydrogen yield was investigated. Pretreatment includes acid and alkali treatments, grinding, heating, ozone and ultrasound methods. After pretreatment organic matters of WAS were solubilized and soluble chemical oxygen demand(SCOD) was increased by 14.6 times. Batch experiments were conducted to investigate the effects of pre-treatment methods and buffer solution, hydrogen partial pressure, and sodium ion on hydrogen production from WAS by using heated anaerobic mixed cultures. Experimental results showed that addition of buffer solution, efficient pre-treatment method with alkali solution, and gas sparging condition markedly increased the hydrogen yield to 0.52 mmol $H_2/g$-DS. 도시 하수처리장에서 수집되는 폐활성 슬러지는 유기성 물질을 다량 함유하고 있는 바이오매스이다. 하지만, 대부분의 연구 결과 폐활성 슬러지를 이용한 생물학적 수소생산율은 매우 낮다고 보고되고 있다. 본 연구에서는 폐활성 슬러지를 산, 알카리 처리, 기계적 처리, 열처리, 오존 처리, 초음파 처리 등의 전처리에 대한 효과를 살펴보았다. 전처리 실험결과, 폐활성 슬러지 내의 유기물질들은 가용화되었으며 $SCOD_{Cr}$값으로 약 14.6배의 증가를 보였다. 열처리된 혐기성 슬러지를 이용하여 폐활성 슬러지로부터 최적의 생물학적 수소생산을 위한 실험은 전처리 방법에 대한 효과 및 완충용액의 효과, 수소분압, 그리고 염소이온의 농도 등에 대하여 회분식 조건에서 살펴보았다. 실험결과 효과적인 전처리 방법 및 완충용액의 첨가, gas sparging 등의 방법에 의한 낮은 수소분압인 경우에 수소생산율이 0.52 mmol $H_2/g$-DS(Dried Solids)로 크게 증가함을 확인하였다.